Simulating faults in a Boeing 737-200 environmental control system using a thermodynamic model - Esperon Miguez, Manuel; Jennions, Ian K.; Escobar, Ignacio Camacho; Hanov, Nile (Prognostics and Health Management Society, 2020)
The Environmental Control Systems (ECS), used to provide air to the aircraft cabin at the correct pressure and temperature, is a key driver of maintenance interruptions for military and civil aircraft. Fault detection is particularly difficult, due to the lack of instrumentation and the ability of the ECS’s control system to mask symptoms. Understanding how component degradation affects measurable thermodynamic parameters is key to developing a condition monitoring system for an ECS. This work focuses on the development of a thermodynamic model of a Boeing 737-200 ECS capable of simulating faults in three types of component: heat exchangers, valves, and water separators. The thermodynamic model has been validated using data collected on a ground-based instrumented B737-200 ECS. The results show how a thermodynamic model can be used to simulate the change of temperatures and pressures across the ECS when components degrade
Keywords: physical modeling; Degradation Model; aircraft systems; thermal systems